A report on the rhizome of Scirpus americanus. - Davis, Florence (1990)
Scirpus americanus, also known as Three-square or Chair-maker's sedge, is one of the more common sedges in temperate North America. Its range extends from Newfoundland to Florida and west to the Pacific, also occurring in part of South America and Europe. It is an inhabitant of wet places, especially sandy shores and shallow waters of up to 1-2.5 foot depths. In this report, I will examine the pattern of rhizomal growth in Scirpus americanus. Some reference will be made to the possible similarities and differences between shoreline and aquatic growth. This species was chosen because it often grows in sand dunes, facilitating excavation and study of the rhizome. Aerial shoots and the demarcation of individual genets are often easily identified, as well. http://deepblue.lib.umich.edu/bitstream/2027.42/54171/1/2606.pdf Description of 2606.pdf : Access restricted to on-site users at the U-M Biological Station.